Ajaran Tasawuf Pada Tarekat Tijanniyah - Fitria, Mahgfirotul (Spiritualita, 2021)
Tarekat is a container or institution that becomes the medium of a person or a people who want to be closer to God and His messengers, for example like the order that will be discussed in this paper, namely the order formed by sheikh Ahmad At-Tijania, or can be called the Tijanniyah order. In the teachings he taught to get closer to Allah Almighty, there are several zikir in different forms, namely zikir in dzimmah, understanding the qualities of divinity and multiplying the reading of Sholawat on prophet Muhammad SAW